The role of nutrients in human neurodevelopment and their potential to prevent neurodevelopmental adversity - Heland, Sarah; Fields, Neville; Ellery, Stacey Joan; Fahey, Michael; Palmer, Kirsten Rebecca (Frontiers in Nutrition, 2022)
Nutritional deficits or excesses affect a huge proportion of pregnant women worldwide. Maternal nutrition has a significant influence on the fetal environment and can dramatically impact fetal brain development. This paper reviews current nutritional supplements that can be used to optimise fetal neurodevelopment and prevent neurodevelopmental morbidities, including folate, iodine, vitamin B12, iron and vitamin D. Interestingly, while correcting nutritional deficits can prevent neurodevelopmental adversity, overcorrecting them can in some cases be detrimental, so care needs to be taken when recommending supplementation in pregnancy. The potential benefits of using nutrition to prevent neuroadversity is shown by promising nutraceuticals, sulforaphane and creatine, both currently under investigation. They have the potential to promote improved neurodevelopmental outcomes through mitigation of pathological processes, including hypoxia, inflammation and oxidative stress. Neurodevelopment is a complex process and whilst the role of micronutrients and macronutrients on the developing fetal brain is not completely understood, this review highlights the key findings thus far.